Pengaruh Lagu Bahasa Inggris Untuk Meningkatkan Kemampuan Bahasa Inggris Terhadap Siswa - Beby Florencia Putri (Journal Of Language Education and Development (JLed), 2023)
Currently, English language skills are the most important thing that students should have. In this world there are many ways that can be used to develop English language skills. One way is by using songs. The aim of the research in this article is to find out how successful the use of songs is in developing English language talent in students. This research uses a qualitative study method. The author obtained some data regarding how songs are used to develop students' level of English by assessing previous research and analyzing several guides such as books, articles, journals and documents that are still related to the discussion being tested. From this, the author can draw the conclusion that using songs as a tool to develop improved English language skills, this is the fastest way to develop students' abilities. therefore many songs can be found easily in student life. So songs can easily help students' listening and pronunciation levels. and this song can also help students in using songs. The use of songs can help students to develop listening and pronunciation skills them which can also add to the vocabulary they have.